Sistem Pendukung Keputusan Kelayakan Ajuan Anggaran Belanja Peralatan Pada Klinik Utama Sari Medika - Prawitasari, Dian; Setiawan, Aries; Pandji Mertha Agung Durya, Ngurah; Nuryanto, Imam; Dian Andika, Arditya; Prasetya, Jaka; Kusumaningrum, Lely; Widjajanto, Budi (Jurusan Teknologi Informasi Universitas Semarang, 2026)
The existence of a very large and varied level of clinical needs supports the leadership to make a selection of equipment purchases by considering the feasibility of the budget proposal value. The existing problem so far is that the approval of budget proposals has not been optimal, namely without considering the priority scale and level of equipment needs submitted, so that many equipment proposals are approved but their functions are not optimal and on the other hand, equipment with a level of function that should be high but not approved. The purpose of this study is to support decision makers in determining the feasibility of approving each equipment expenditure budget proposal to produce choices that are in accordance with the level of needs and interests of each section. The method used is simple additive weighting with a test result level of 90%.